2019
DOI: 10.1108/jcm-04-2018-2657
|View full text |Cite
|
Sign up to set email alerts
|

Reducing consumer loneliness through brand communities

Abstract: Purpose The purpose of this paper is to examine the role of belonging to brand communities in improving consumer well-being and brand evaluations. Design/methodology/approach Two studies were conducted. Study 1 manipulates the framing of a brand to be either socially- or product-oriented and measures brand community joining intentions based on underlying levels of consumer loneliness and need to belong. Study 2 manipulates feelings of belongingness with a brand community and measures its impact on relatednes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 32 publications
0
22
0
1
Order By: Relevance
“…This cluster contains three key themes: marketplace relationships , mobility and disability issues , and consumer well-being . Being linked to the central theme of affiliation motivation, this cluster addresses lonely consumers’ compensatory attachment to marketplace relationships with salespersons, brand communities or online celebrities (e.g., parasocial and telepresence) [ 56 , 57 , 58 ]. A particular emphasis is placed on the well-being of the disadvantaged consumers or the elderly, who are vulnerable to loneliness and social isolation [ 59 , 60 ], especially given the current situation of COVID-19 [ 11 , 61 ].…”
Section: Lonely Consumers: Psychological Commercial and Social Immentioning
confidence: 99%
See 1 more Smart Citation
“…This cluster contains three key themes: marketplace relationships , mobility and disability issues , and consumer well-being . Being linked to the central theme of affiliation motivation, this cluster addresses lonely consumers’ compensatory attachment to marketplace relationships with salespersons, brand communities or online celebrities (e.g., parasocial and telepresence) [ 56 , 57 , 58 ]. A particular emphasis is placed on the well-being of the disadvantaged consumers or the elderly, who are vulnerable to loneliness and social isolation [ 59 , 60 ], especially given the current situation of COVID-19 [ 11 , 61 ].…”
Section: Lonely Consumers: Psychological Commercial and Social Immentioning
confidence: 99%
“…Literature in this regard has shown that consumers develop meaningful relationships with the brands, consumption communities, service providers and in-store salespersons that buffer interpersonal insecurity and compensate consumers’ fundamental need for belongingness [ 1 , 57 , 59 ]. For example, Snyder and Newman [ 57 ] showed that consumers treat brand communities as a viable avenue for social connections. The traditional communities, which are geographically-bound, are in decline in the fragmented modern society, whereas the brand communities are fast-growing on social media, which create social relatedness and ease loneliness [ 1 ].…”
Section: Lonely Consumers: Psychological Commercial and Social Immentioning
confidence: 99%
“…They also propose that customer factors (e.g., customer expertise) play their roles in driving OBC engagement. For example, Snyder and Newman [37] indicated that loneliness motivates consumers' brand community participation. In light of their framework, we reviewed the literature on the antecedents of OBC engagement in Table 1.…”
Section: Brand Community Engagementmentioning
confidence: 99%
“…Bagozzi and Dholakia [44] found that the identification of the group of consumers of a brand leads people to participate in the brand community. Within OBCs, consumers usually experience a great deal of meaningful social interaction and build close social relationship such as trust and intimacy [4,37,62]. Therefore, people usually tend to participate in OBCs for social purposes [37,41].…”
Section: The Effect Of Brand Community Gratificationmentioning
confidence: 99%
See 1 more Smart Citation